Hollow Rutile Cuboid Arrays Grown on Carbon Fiber Cloth as a Flexible Electrode for Sodium‐Ion Batteries. (9th September 2020) - Wang, Chao; Zhang, Jiansheng; Wang, Xianfen; Lin, Chunfu; Zhao, Xiu Song
Abstract: Flexible electrodes with high charge storage capacity, low solid‐state diffusion resistance toward charges, and excellent mechanical properties are needed for fabricating flexible energy storage devices. In this paper, an approach is described to synthesize a composite material with hollow rutile TiO2 cuboid arrays supported on carbon fiber cloth (H‐TiO2 @CFC). This composite material is used as a self‐supporting and binder‐free anode for sodium‐ion storage, delivering reversible charge capacities of 287.3 at 0.1 C and 103.3 mAh g −1 at 50 C, respectively. The observed excellent electrochemical performance of the H‐TiO2 @CFC electrode is mainly attributed to its unique architecture, which facilitates ion transport, improves electron conductivity, and enables active surface reactivity toward sodium ions. In situ X‐ray diffraction characterization results reveal a nearly zero strain structure of the hollow rutile TiO2 in H‐TiO2 @CFC against electrochemical cycling. An analysis of the charge storage mechanism reveals a significant pseudocapacitance contribution to the charge storage, accounting for the observed high‐rate performance of the electrode. A flexible full cell fabricated with the H‐TiO2 @CFC as the anode and Na3 V2 (PO4 )3 as the cathode exhibits both excellent electrochemical properties and flexibility against mechanical deformation, demonstrating the great promise of the H‐TiO2 @CFC composite material for flexible battery cells. Abstract : A free‐standing composite consisting of hollow rutile cuboid arrays supported on carbon fiber cloth delivers remarkable rate performance and excellent cycling stability as an anode for sodium‐ion batteries. The architecture of the composite facilitates charge transport and electron conductivity, thus affording excellent rate capability and mechanical flexibility against bending as tested with a full cell.